Characterization of CoCas9 nuclease from Capnocytophaga ochracea - A. Vasileva; P. Selkova; A. Arseniev; M. Abramova; N. Shcheglova; O. Musharova; I. Mizgirev; T. Artamonova; M. Khodorkovskii; K. Severinov; I. Fedorova (RNA Biology)
Cas9 nucleases are widely used for genome editing and engineering. Cas9 enzymes encoded by CRISPR-Cas defence systems of various prokaryotic organisms possess different properties such as target site preferences, size, and DNA cleavage efficiency. Here, we biochemically characterized CoCas9 from Capnocytophaga ochracea, a bacterium that inhabits the oral cavity of humans and contributes to plaque formation on teeth. CoCas9 recognizes a novel 5’-NRRWC-3’ PAM and efficiently cleaves DNA in vitro. Functional characterization of CoCas9 opens ways for genetic engineering of C. ochracea using its endogenous CRISPR-Cas system. The novel PAM requirement makes CoCas9 potentially useful in genome editing applications.